Online and Distance Education for a Connected World - Amrane-Cooper, Linda; Baume, David; Brown, Stephen; Hatzipanagos, Stylianos; Powell, Philip; Sherman, Sarah; Tait, Alan (UCL Press, 2023)
Learning at a distance and learning online are growing in scale and importance in higher education, presenting opportunities for large scale, inclusive, flexible and engaging learning. These modes of learning swept the world in response to the Covid-19 pandemic. The many challenges of providing effective education online and remotely have been acknowledged, particularly by those who rapidly jumped into online and distance education during the crisis. This volume, edited by the University of London's Centre for Online and Distance Education, addresses the practice and theory of online and distance education, building on knowledge and expertise developed in the University over some 150 years. The University is currently providing distance transnational education to around 50,000 students in more than 180 countries around the world. Throughout the book, contributors explore important principles and highlight successful practices in areas including course design and pedagogy, online assessment, open education, inclusive practice, and enabling student voice. Case studies illustrate prominent issues and approaches. Together, the chapters offer current and future leaders and practitioners a practical, productive, practice- and theory-informed account of the present and likely future state of online and distance higher education worldwide.